The Effectiveness of Interventions to Reduce the Nurses’ Distractions during Medication Administration: A Systematic Review - Chandra Apriadi Panduwal; E. C. Bilaut (Jurnal Ners, 2019)
Introduction: Nurses constitute the largest group of health professionals who work in the hospital setting and most of the medications in the setting are administered by nurses. Errors related to medication conducted by a nurse frequently occur during medication administration. Interruptions or distractions during medication administration have been identified as significant contributory factors to medication administration errors (MAEs).Methods: This systematic review critically reviewed the evidence of the effectiveness of the interventions that aim to reduce nurse interruptions or distractions during medication administration. The search for the relevant literature was conducted in August 2018 using three databases; Medline, Cinahl and Embase.Results: Nineteen full text articles were retrieved and reviewed, and 7 articles were included in this review. Five of these studies showed evidence of a reduction in the interruption or distraction rates in post-intervention measurements, while 4 studies reported a statistically significant reduction in the interruption or distraction rates, with p values between 0.0005 and 0.002.Conclusion: There was limited evidence available to support the effectiveness of the interventions in terms of either reducing the interruptions or distractions of the nurses during the medication administration or in terms of reducing the medication administration error rates.